Private higher education : an international bibliography - Maldonado, Alma; Cao, Yingxia; Altbach, Philip G.; Levy, Daniel C.; Zhu, Hong (Publication series (Boston College. Center for International Higher Education), 2004)
This research project has been supported by the Ford Foundation, the Lynch School of Education at Boston College, and the Program of Research on Private Higher Education at the University at Albany.